Stability Characteristics of Wing Span and Sweep Morphing for Small Unmanned Air Vehicle: A Mathematical Analysis. (3rd July 2020) - Muhammad Umer, Hafiz; Maqsood, Adnan; Riaz, Rizwan; Salamat, Shuaib
Abstract : Morphing aircraft are the flight vehicles that can reconfigure their shape during the flight in order to achieve superior flight performance. However, this promising technology poses cross-disciplinary challenges that encourage widespread design possibilities. This research aims to investigate the flight dynamic characteristics of various morphed wing configurations that can be incorporated in small-scale UAVs. The objective of this study was to analyze the effects of in-flight wing sweep and wingspan morphing on aerodynamic and flight stability characteristics. Longitudinal, lateral, and directional characteristics were evaluated using linearized equations of motion. An open-source code based on Vortex Lattice Method (VLM) assuming quasi-steady flow was used for this purpose. Trim points were identified for a range of angles of attack in prestall regime. The aerodynamic coefficients and flight stability derivatives were compared for the aforementioned morphing schemes with a fixed-wing counterpart. The results indicated that wingspan morphing is better than wing sweep morphing to harness better aerodynamic advantages with favorable flight stability characteristics. However, extension in wingspan beyond certain limits jeopardizes the advantages. Dynamically, wingspan and sweep morphing schemes behave in an exactly opposite way for longitudinal modes, whereas lateral-directional dynamics act in the same fashion for both morphing schemes. The current study provided a baseline to explore the advanced flight dynamic aspects of employed wing morphing schemes.